Keanekaragaman Serangga Hama dan Musuh Alami Pada Tumpangsari Tanaman Jagung dan Kacang Tanah di Desa Oemasi Kecamatan Nekamese Kabupaten Kupang - Seviana Jebe; Titik Sri Harini; Rika Ludji; Agustina Etin Nahas (Wana Lestari, 2024)
Maize and groundnuts are commodities that are always cultivated by farmers, including in East Nusa Tenggara Province. The cropping system of these two commodities also varies, both with monoculture and intercropping patterns. The main obstacle that is often faced in the cultivation of corn and peanut plants is the attack of pests and pathogens that cause disease. This study aims to determine the types of insect pests and natural enemies in intercropping corn and peanut plants, the population of each type of insect and the diversity index of insect pests and natural enemies in intercropping corn and peanuts. This study used a survey method with direct observation techniques on each trap. Sampling techniques were carried out using yellow traps and tools in the form of swing nets. From the sampling results found 7 species of pests and 4 species of natural enemies in intercropping corn and peanuts in Oemasi Village, The most pest population found in intercropping corn and peanuts is Helicoverpa armigera and the least is Anoplocnemis phasiana The population of natural enemies found in intercropping corn and peanuts is Solenopsis geminata, The diversity index of insect pests and natural enemies in intercropping corn and peanuts is included in the medium category.